Analysis of Damage Rod String Components in Sucker Rod Pump in The Field SS - Fitrianti Fitrianti; Anwar Haryono (Journal of Earth Energy Engineering, 2018)
Field SS is a Heavy Oil field which means high viscosity oil making it difficult to flow. Therefore, artificial lift was used in this field to help lifting the high viscosity fluid, i.e. sucker rod pump (SRP). In the last several years, problem of the damage to the rod string was frequently occur. Rod string damage is usually indicated by the occurrence of broken or detached components. In order to overcome the damage of rod string components on the sucker rod pump, several parameters that causes rod string damage in 41 well samples in the field SS were analyzed and then recommendations were made as an alternative to minimize the occurrence of rod string damage. After analyzing the parameters that can cause rod string damage on 41 well samples in SS field, the cause of the breakdown of rod string is fluid pounding for 37 samples well, while the causes for 4 samples of other wells is not detected. After that, recommendation efforts is done, like size down pump speed and stroke length for 9 samples of wells, size down pump size and pump speed for 6 samples of wells and size down pump speed for 22 samples well. As for the undetected cause 4 samples of wells, is recommended to do proactive well service.